Motivasi pembelajaran jarak jauh: studi kasus mahasiswa dan dosen pendidikan matematika di Nusa Tenggara Timur - Lipat, Maria Reginalis (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
The Covid-19 pandemic has wreaked havoc on people’s lives. Life that has been built in togetherness or groups. During this pandemic, people are prohibited from gathering together. The result of this pandemic is that all schools, universities and colleges are closed. All teaching and learning activities are carried out online. One of the universities that conduct online learning is the Larantuka Teacher Training and Technology Institute (IKTL). Here the author wants to do research on online learning activities carried out by IKTL. This study aims to (1) determine the motivation for distance learning for students in IKTL; (2) knowing the obstacles that occur during the distance lecture process and how to overcome the obstacles during the distance learning process. In this study, the authors also use qualitative research that uses a questionnaire to collect data. The research was conducted at the Larantuka Institute of Teacher Training and Technology, East Flores, NTT. The results showed that students’ motivation in learning online was because they got bad grades. And the obstacles faced by students and lecturers are the limited internet quota and blackouts of electric lights. To overcome these obstacles, the government and the campus must work together to launch this online education. It is interesting that almost some of the students and lecturers interact with each other in the lecture so that the study runs well.